Land suitability analysis for cereal-forage legume mixed cropping system - Tesfaye, Getachew; Tibebe, Degefie; Mesfin,Tewodros; Ayele, Kalkidan; Abera, Wuletawu; Tamene, Lulseged D. (2024)
Ethiopia's highland mixed crop-livestock farming system is one of the country's primary agricultural systems, where crop and livestock production is integrated. However, Ethiopia's mixed farming system, which is dominated by resource-poor smallholder farmers, is frequently confronted with feed shortages and land degradation in the form of soil erosion and nutrient depletion, resulting in low agricultural production. Assuring sustainable agricultural output (both from crop and livestock sub-sector) in the mixed crop-livestock system is becoming a key challenge. It is thus necessary to introduce environmentally friendly approaches that integrate crop, livestock, and soil management practices and help to sustainably increase agricultural production in the country's low-input mixed farming systems. Accordingly, scholars have suggested that incorporating forage-legumes into cereal-based cropping systems is a viable strategy for enhancing the sustainability of smallholder farmers' livelihoods by improving soil fertility, crop and livestock productivity, and soil management. However, the information essential for which food crop should combine with which forage legume and where, to achieve sustainable increase in agricultural production at smallholder farmer plots, is not yet well reported. Thus, the main objective of this study was to assess the suitability of land for mixed cereal-forage legume cropping system. Four major cereal crops including Wheat (Triticum aestivum), Barley (Hordeum vulgare), Maize (Zea mays), and Teff (Eragrostis tef) and commonly used forage-legumes i.e., Lablab (Lablab purpureus), Alfalfa (Medicago sativa), Cowpea (Vigna unguiculata), and Common Vetch (Vicia sativa) of Ethiopia were selected in this study. A weighted sum overlay analysis was made to map the suitability of land for each target crops. An optimization approach, based on the economic and biophysical benefits of each crop, were used to generate multi-crop suitability map. In this report only a preliminary result for the suitability analysis of cereal crops is provided. The suitability mapping of legume-forage and mixed cereal-forage legume will resume.